Novel targeted therapy for acute myeloid leukemia with a dual FLT3 and JAK2 inhibitor - Lou Yin-jun (Acta Pharmacologica Sinica, 2016)
Novel targeted therapy for acute myeloid leukemia with a dual FLT3 and JAK2 inhibitor